2016
DOI: 10.1186/s13612-016-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Why won’t it Stick? Positive Psychology and Positive Education

Abstract: Following the launch of the positive psychology movement teachers and educators emerged as early adopters of this fledgling science. This approach was called positive education. It describes scientifically validated programs from positive psychology, taught in schools, that have an impact on student well-being. The growing body of evidence about the reach of positive psychology has formed a convincing case to consider well-being an operational goal for educational systems. It is argued that this goal is pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 32 publications
0
50
0
9
Order By: Relevance
“…Two prominent meta-analyses concluded that positive psychology interventions can have a modest impact on increasing well-being and decreasing ill-being [45, 46]. However, when the methodological shortcomings of these analyses are addressed (e.g., small sample size bias), positive psychology interventions seem to have no effect or at most a small impact on ill-being and well-being [47]. In particular, the effect sizes approach zero when small sample size bias is accounted for.…”
Section: Food Intake Viewed As a Positive Psychology Interventionmentioning
confidence: 99%
“…Two prominent meta-analyses concluded that positive psychology interventions can have a modest impact on increasing well-being and decreasing ill-being [45, 46]. However, when the methodological shortcomings of these analyses are addressed (e.g., small sample size bias), positive psychology interventions seem to have no effect or at most a small impact on ill-being and well-being [47]. In particular, the effect sizes approach zero when small sample size bias is accounted for.…”
Section: Food Intake Viewed As a Positive Psychology Interventionmentioning
confidence: 99%
“…In short, while there is emerging evidence regarding the efficacy of PPI's in improving wellbeing and reducing depressive symptoms, greater attention needs to be paid to their design and implementation in real world and complex settings (e.g., White 2016). We now demonstrate that the program development and implementation science literature offers significant utility in this regard.…”
Section: Introductionmentioning
confidence: 78%
“…This introductory article aims to highlight the studies in this special issue and motivate readers to appreciate and build on these contributions. White (2016) suggested that we must provide scientific evidence, organizational benefits, and philosophical arguments to support the integration of wellbeing in education. Therefore, we intend to provide suggestions following White's opinion.…”
Section: Future Horizons For Positive Education Researchmentioning
confidence: 99%